Dissimilar Similitudes : Devotional Objects in Late Medieval Europe - Bynum, Caroline Walker (Book collections on Project MUSE., 2020)
"Between the twelfth and the sixteenth centuries, European Christians used in worship a plethora of objects, not only prayer books, statues, and paintings but also pieces of natural materials, such as stones and earth, considered to carry holiness, dolls representing Jesus and Mary, and even bits of consecrated bread and wine thought to be miraculously preserved flesh and blood. Theologians and ordinary worshippers alike explained, utilized, justified, and warned against some of these objects, which could carry with them both anti-Semitic charges and the glorious promise of heaven. Their proliferation and the reaction against them form a crucial background to the European-wide movements we know today as "reformations" (both Protestant and Catholic). In a set of independent but inter-related essays, Caroline Bynum considers some examples of such holy things, among them beds for the baby Jesus, the headdresses of medieval nuns, and the footprints of Christ carried home from the Holy Land by pilgrims in patterns cut to their shape or their measurement in lengths of string. Building on and going beyond her well-received work on the history of materiality, Bynum makes two arguments, one substantive, the other methodological. First, she demonstrates that the objects themselves communicate a paradox of dissimilar similitude-that is, that in their very details they both image the glory of heaven and make clear that that heaven is beyond any representation in earthly things. Second, she uses the theme of likeness and unlikeness to interrogate current practices of comparative history. Suggesting that contemporary students of religion, art, and culture should avoid comparing things that merely "look alike," she proposes that humanists turn instead to comparing across cultures the disparate and perhaps visually dissimilar objects in which worshippers as well as theorists locate the "other" that gives their religion enduring power"--